Effect of biogenic jarosite on the bio-immobilization of toxic elements from sulfide tailings. (November 2020) - Piervandi, Zeinab; Khodadadi Darban, Ahmad; Mousavi, Seyyed Mohammad; Abdollahy, Mahmoud; Asadollahfardi, Gholamreza; Funari, Valerio; Dinelli, Enrico; Webster, Richard David; Sillanpää, Mika
Abstract: The discharge of toxic elements from tailings soils in the aquatic environments occurs chiefly in the presence of indigenous bacteria. The biotic components may interact in the opposite direction, leading to the formation of a passivation layer, which can inhibit the solubility of the elements. In this work, the influence of jarosite on the bio-immobilization of toxic elements was studied by native bacteria. In batch experiments, the bio-immobilization of heavy metals by an inhibitory layer was examined in the different aquatic media using pure cultures of Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans . A variety of analyses also investigated the mechanisms of metals bio-immobilization. Among different tests, the highest metal solubility yielded 99% Mn, 91% Cr, 95% Fe, and 78% Cu using A. ferrooxidans in 9KFe medium after ten days. After 22 days, these percentages decreased down to 30% Mn and about 20% Cr, Fe, and Cu, likely due to metal immobilization by biogenic jarosite. The formation of jarosite was confirmed by an electron probe micro-analyzer (EPMA), X-ray diffraction (XRD), and scanning electron microscope (SEM). The mechanisms of metal bio-immobilization by biogenic jarosite from tailings soil confirmed three main steps: 1) the dissolution of metal sulfides in the presence of Acidithiobacillus bacteria; 2) the nucleation of jarosite on the surface of sulfide minerals; 3) the co-precipitation of dissolved elements with jarosite during the bio-immobilization process, demonstrated by a structural study for jarosite. Covering the surface of soils by the jarosite provided a stable compound in the acidic environment of mine-waste. Graphical abstract: Image 1 Highlights: The samples were collected from Sarcheshmeh copper complex tailings dam, Iran. Pure strains of A. ferrooxidans and A. thiooxidans were used in bioleaching. The highest elements extraction took place by A. ferrooxidans after 10 days. Metals solubility decreased significantly after 22 days due to immobilization. Results demonstrated the stabilization of metals with the structure of jarosite.